2021
DOI: 10.3892/ol.2021.12787
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and immunological roles of Fc fragment of IgG binding protein in colorectal cancer

Abstract: Valuable diagnostic and prognostic biomarkers are urgently needed for colorectal cancer (CRC), which is one of the leading causes of mortality worldwide. Previous studies have reported altered expression of a mucin-like protein Fc fragment of IgG binding protein (FCGBP) in various types of cancer, but its potential diagnostic, prognostic and immunological roles in CRC remain to be determined. Therefore, the aim of current study was to investigate the potential roles of FCGBP in CRC. The present study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In the other work, FCGBP correlates positively with M2 macrophage polarization and negatively with M1 polarization (67). This suggests that FCGBP is also involved in regulating the infiltration of immune cells in the tumor microenvironment of ovarian cancer, where it may be a valuable marker for prognostic evaluation (67,75). In CRC, FCGBP abundance shows inverse correlation with tumor purity and macrophage expression but coincides with a high number of B cells, suggesting that FCGBP may be involved in humoral immune responses in this cancer (76).…”
Section: Effects On Tumor Immune Responsesmentioning
confidence: 84%
See 1 more Smart Citation
“…In the other work, FCGBP correlates positively with M2 macrophage polarization and negatively with M1 polarization (67). This suggests that FCGBP is also involved in regulating the infiltration of immune cells in the tumor microenvironment of ovarian cancer, where it may be a valuable marker for prognostic evaluation (67,75). In CRC, FCGBP abundance shows inverse correlation with tumor purity and macrophage expression but coincides with a high number of B cells, suggesting that FCGBP may be involved in humoral immune responses in this cancer (76).…”
Section: Effects On Tumor Immune Responsesmentioning
confidence: 84%
“…First, the elevated expression of FCGBP may reflect pathophysiologic changes in Crohn's disease and ulcerative colitis (40), but the mRNA and protein expression of FCGBP are decreased in colorectal adenomas and cancers. Furthermore, cancer progression and the formation of metastatic lesions leads to further significant reduction (75), highlighting the role of FCGBP in oncogenesis and cancer progression. The second one is that the alternative splicing of FCGBP mRNA is detected in lung cancer (44), hepato-cholangiocarcinoma (80), CRC (75,81), and brain arteriovenous malformations (42).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly low expression of FCGBP has been observed in intestinal inflammation and tumors, such as ulcerative colitis (24), colorectal adenoma (25), and colorectal cancer (26)(27)(28). In addition, FCGBP is also down-regulated in multiple tumors (12,13,29,30), and this imbalance of expression due to different functions that may be involved in different tumors. Through the TCGA and CGGA databases, we first found that FCGBP was highly expressed in glioma tissues and had a significant positive correlation with the grade of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Initially reported as an important component of immunological mucosal defences [ 60 ], FCGBP gained more interest recently due to the fact of its variable expression and contradictory roles in different types of malignancies, where it seems to be involved in the immune response associated with cancer development [ 61 , 62 , 63 , 64 ]. Of note, it has been shown to be a metastasis-associated gene in IDH wild-type gliomas [ 65 ] and a tumour antigen in low-grade gliomas [ 61 ].…”
Section: Discussionmentioning
confidence: 99%